Bilateral eventration of sciatic nerve - T Sharma; RK Singla; M Lalit (Journal of Nepal Medical Association, 2010)
During routine dissection of a 60 years male cadaver, it was observed that the two divisions of sciatic nerve were separate in the gluteal region on both the sides with the tibial nerve passing below the piriformis and the common peroneal nerve piercing the piriformis muscle. The abnormal passage of the sciatic nerve (SN), the common peroneal nerve (CPN), and the tibial nerve (TN), either through the piriformis or below the superior gemellus may facilitate compression of these nerves. Knowledge of such patterns is also important for surgeons dealing with piriformis syndrome which affects 5-6% of patients referred for the treatment of back and leg pain. A high division may also account for frequent failures reported with the popliteal block.